THE PLACE AND SIGNIFICANCE OF THE FINTECH INDUSTRY IN THE DIGITAL ECONOMY - Мороз, Владислав; Атаманчук, З. (SWorldJournal, 2023)
The article clarifies the place and role of the fintech industry in the digital economy, substantiates the importance of new technologies in the development of economic systems. Variants of using of fin-tech company services that can improve service and e